Penyuluhan dan Pemeriksaan Penyakit Diabetes di Desa Mulyoagung-dau Kabupaten Malang - Sugeng Hadi Susilo; Umi Anis Ro’isatin; Agus Setiawan; Zahratul Jannah; Samsul Hadi (CV. Creative Tugu Pena, 2021)
The problem in community service that will be carried out is how to provide health education, especially for diabetes, acid and cholesterol to the community. The purpose of this idea or idea is to provide counseling and public health checks in Mulyoagung Village, Dau District. Malang especially RT 01 RW 03. In this service activity uses the following methods: 1. Coordinating with prospective participants of health education and examination. 2. Preparing counseling materials, health checks and designing activities. 3. Carry out counseling and health checks. 4. Evaluating counseling and health checks. 5. Observing counseling and health checks. Keywords: Counseling, Examination Diabetes, Health Education.